Management of ecosystems alters vector dynamics and haemosporidian infections - van Hoesel, Willem (Sci Rep, 2019)
The presence of insect vectors is a key prerequisite for transmission of vector-borne disease such as avian haemosporidians. In general, the effects of land use change on Diptera vectors are not well studied; the response of vectors to forest management depends on vector species, as has been shown previously for the birds. We tested if abundance of insects from different Diptera families and haemosporidian infection are affected through alteration of habitat structural variables (measured by LiDAR) and forest management intensities. We identified higher large-scale variation of female insect abundance in northeastern than in southwestern Germany. Unmanaged forest stands had higher Diptera insect abundances. We found that abundance of female Diptera increased with the amount of forest gaps but decreased in forest plots with more south facing aspect, higher habitat structural heterogeneity, temperature and humidity. We found that haemosporidian infections in Diptera insects increased with increased management intensity and more canopy structural diversity (e.g., amount of edge habitat), but decreased with a denser shrub layer, deeper leaf litter and higher humidity (characteristics for unmanaged forest stands). Although higher forest management intensity decreased vector abundance, the haemosporidian infections in the vectors increased, indicating a significant effect of forest management on disease dynamics.